Lifestyle related factors & impact of metabolic syndrome on quality of life, level of functioning & self-esteem in patients with bipolar disorder & schizophrenia - Malhotra, Nidhi (Indian J Med Res, 2016)
BACKGROUND & OBJECTIVES: Though studies have reported high prevalence rates of metabolic syndrome among patients with bipolar disorder (BPAD) and schizophrenia, there is lack of data on the impact of the same on the patients’ life. This study was aimed to assess the lifestyle related factors associated with metabolic syndrome (MetS) and to study the impact of MetS on functioning and quality of life (QOL) in patients with BPAD and schizophrenia. METHODS: A total of 102 patients with BPAD and 72 patients with schizophrenia attending the output unit of a tertiary care hospital in north India were evaluated for MetS. These patients were assessed on Health Promoting Lifestyle Profile scale II (HPLP II), World Health Organization QOL -Bref Version (WHOQOL-Bref), Impact of Weight on Quality of Life- Lite version (IWOQOL -Lite), Body weight, Image and Self-esteem Evaluation questionnaire (BWISE), Obesity-related Problem scale (OP scale) and Global Assessment of Functioning (GAF) scale. RESULTS: MetS was associated with lower scores on domains of health responsibility and nutrition habit domain on HPLP-II scale in both groups, and additionally on physical activity and stress management domain in BPAD group. On WHOQOL-Bref, MetS was associated with lower scores on the domains of physical and psychological health in both groups. On IWQOL–Lite, scores on personal distress and self esteem domains were higher in those with obesity in both groups and also on physical activity domain in schizophrenia group. Those with MetS had lower level of functioning as measured by GAF in schizophrenia group. Fulfillment of higher number of criteria of MetS correlated with poorer quality of life and higher problems in both groups. INTERPRETATION & CONCLUSIONS: Many modifiable lifestyle factors increase the risk of MetS. MetS was found to be associated with poorer QOL in patients with BPAD and schizophrenia; in addition, obesity led to poor self-esteem and excessive personal distress.